Frontispiece: Reverse Spin‐Crossover and High‐Pressure Kinetics of the Heme Iron Center Relevant for the Operation of Heme Proteins under Deep‐Sea Conditions. Issue 43 (20th October 2014) - Troeppner, Oliver; Lippert, Rainer; Shubina, Tatyana E.; Zahl, Achim; Jux, Norbert; Ivanović‐Burmazović, Ivana
<x xml:space="preserve">Abstract</x> High‐Pressure Chemistry In their Communication on page 11452 ff., I. Ivanović‐Burmazović et al. report the effect of confined space around a heme iron center.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>